2021
DOI: 10.1111/cch.12908
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative comparison of parent and childcare provider perceptions of communication and family engagement in children's healthy eating and physical activity

Abstract: Background: Parents and childcare providers play a substantial role in the development of health behaviours among the children they care for. In order to ensure the optimal growth and development of children, communication and family engagement in childcare is critical. Previous studies examining parent or provider perceptions about healthy eating or physical activity have explored these concepts individually and/or have only included only parents or providers. Therefore, the purpose of this study was to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
(73 reference statements)
1
2
0
Order By: Relevance
“…It has often been suggested that the more teachers promote and demonstrate physical activity the more likely children are to be physically active (Bruijns et al, 2022a ; Fossdal et al, 2018 ; Froehlich Chow & Humbert, 2014 ; Kippe et al, 2021 ). Most teachers in our study believed they helped children to be more physically active during preschool and stated they even had more of an impact on children’s daily physical activity levels than the children’s parents, which is similar to findings from other studies (Derscheid et al, 2010 ; Dinkel et al, 2022 ; Kippe et al, 2021 ). Although teachers identified themselves as key role models to children’s physical activity, children still spent up to 60% of their outdoor play time being inactive; engaged in activities such as sitting on fixed equipment, despite outdoor play time being intended for children to achieve MVPA.…”
Section: Discussionsupporting
confidence: 90%
“…It has often been suggested that the more teachers promote and demonstrate physical activity the more likely children are to be physically active (Bruijns et al, 2022a ; Fossdal et al, 2018 ; Froehlich Chow & Humbert, 2014 ; Kippe et al, 2021 ). Most teachers in our study believed they helped children to be more physically active during preschool and stated they even had more of an impact on children’s daily physical activity levels than the children’s parents, which is similar to findings from other studies (Derscheid et al, 2010 ; Dinkel et al, 2022 ; Kippe et al, 2021 ). Although teachers identified themselves as key role models to children’s physical activity, children still spent up to 60% of their outdoor play time being inactive; engaged in activities such as sitting on fixed equipment, despite outdoor play time being intended for children to achieve MVPA.…”
Section: Discussionsupporting
confidence: 90%
“…Although childcare teachers are not directly responsible for the children’s healthcare, they have a role in supporting families in providing the best care for their children. 5,13 They are often the first to advise parents on development and health issues. 14…”
Section: Discussionmentioning
confidence: 99%
“…Childcare teachers can play a relevant role in this process as they collaborate closely with families, supporting parents on children’s development, education, and health issues. 5 However, to properly advise parents about their children’s weight issues, teachers must be able to identify children who might be at increased risk of non-healthy weight. Although we could not find any study about childcare teachers’ perception of children’s weight, earlier contributions showed that teachers were generally skeptical about the definition of overweight in young children, were unsure about how to address this issue, 6 and had difficulty accepting that a child has overweight even when a healthcare professional identified this condition.…”
Section: Purposementioning
confidence: 99%
“…For example, a meta‐analysis of parenting interventions found that changes in parenting practices, parenting knowledge, and parent–child interactions led to substantial changes in child development and health outcomes (Jeong et al, 2021). The impact of parenting practices may be especially profound for young children, who are more likely to spend more time with their parents and rely on them for their basic social–emotional and physical needs (Cui et al, 2018; Dinkel et al, 2022; Sulik et al, 2015). For example, a longitudinal study showed the impact of parenting on children's socio‐emotional outcomes was strongest at 3 years old and predicted children's externalizing behaviors at age 7 years (Sulik et al, 2015).…”
Section: Introductionmentioning
confidence: 99%